ANALISIS KEBUTUHAN PARKIR PENGEMBANGAN RUMAH SAKIT ACHMAD MOCHTAR BUKITTINGGI - Bayu Budi Irawan; Yossyafra Yossyafra; Momon Momon (Construction and Material Journal, 2021)
Achmad Mochtar Hospital (RSAM) Bukittinggi is conducting to develop the Community’s needs for health services. The service development is carried out by adding more patient beds. This will certainly have an impact on the need for available parking spaces at the hospital. Based on increased number of patients, it is necessary to analyze the parking needs at the RSAM. The purpose of this study is to identify the volume of parking vehicles, parking accumulation, and the capacity of available parking spaces, as well as to evaluate the parking space requirements in the Hospital area. Data were collected by surveying parking locations in the Hospital area. The analysis method used the Technical Guidelines for the Implementation of Parking Facilities issued by the Director General of Land Transportation Number: 272/HK.105/DRJD/96. Based on the survey results, the highest parking volume in segment 1 is 25 units of private cars and 3 motorcycles, in segment 2 is 11 units of private cars and 14 units of motorcycles, and segment 3 is 14 units of private cars and 37 units of motorcycles and 3 units of non-motorized vehicles. The accumulation of parking for segment 1 is 109 vehicles (10.00 WIB), segment 2 is 98 vehicles (10.45 WIB) and segment 3 is 215 vehicles (11.45 WIB). The parking space capacity in the Hospital area is 152 SRP for a car or the equivalent of 108 SRP (Parking Space Unit) for a private car (80 SRP Off-street and 28 SRP On-street) and 310 SRP for a motorcycle (270 SRP Off-street and 40 SRP On-street). The addition of a new Emergency Room for public service activities (6,000 m2) causes an additional need for 90 SRP private car parking Based on the comparison between the availability and the need for parking, it is found that there is a shortage of parking space of 70 SRP at the hospital parking area. It can be optimized in segment 1, namely the location of the Emergency Room and Ambun Pagi. Keywords: Hospital Parking Area, Parking Volume, Parking Capacity.